DEVELOPING THE ENTREPRENEURSHIP INCUBATOR MODEL TO INCREASE STUDENTS INDEPENDENCE OF ENTREPRENEURSHIP MENTALITY - Suranto Suranto; Rahmawati Rahmawati (Journal of Indonesian Economy and Business (JIEB), 2013)
This research aims to develop a model of entrepreneurial incubator for students in entrepreneurship learning. The model developed by the incubator includes: the empowerment of learners, the concept of problem, problem solution, through the structure of the incubator models doing, empowering, facilitating, and evaluating. This research was a research and development. The steps taken in the development of the model were: (1) designing a model, designing questionnaires, and validating the model, by measuring the goodness of fit; (2) testing the model to measure the applied model. In model validation, the data were collected from 130 students who got incubator treatment selection using the simple random sampling technique. The instrument used for data collection was a questionnaire. The data were analysied using the concept of SEM (Structural Equation Modeling). The method used in experimental field trials was the experimental group and control group (pretest-posttest control group design). The subjects of the tryout were 75 students of informatics engineering course who were not the subjects of the incubator program (the control group) and 75 students of chemistry education, chemistry, mathematics education, mathematics, biology education, and biology were referred to as the experimental group (program subject to the incubator). The data were collected through interviews and questionnaires. The data were analyzed using t-test trials to find out a significant difference in the behavior of the experimental group and control group. The results of the study of the entrepreneurship incubator model development is otherwise valid according to the probability (p) 0.0685, Goodness of Fit Model (GFI) 0.8256, Adjusted Goodness of Fit Index (AGFI) 0.7706, Comparative Fit Index (CFI) 0.9883, and the Root Mean Square Error of Approximation (RMSEA) 0.054. This model is considered effective because it can increase the independence of learners. The result of the confirmatory analysis (CFA) shows that each latent variable is proved to be formed by the manifests of one dimension. The model is applied to have a positive impact on enhancing thestudents tendency in mental independence, after receiving treatment assistance incubators. Latent variable-power is reflected by the manifest: (a) the technical capabilities in writing, (b) awareness for entrepreneurship, (c) motivation for entrepreneurship, (d) the excess of self to self-employed, (e) the lack of self to self-employed, (f) access to other party to entrepreneurship, and (g) networking for entrepreneurship. While professionals have a manifest latent variables: (a) believing in themselves to entrepreneurship, (b) being independent for entrepreneurship, (c) being resilient and determined to entrepreneurship, (d) perseverance up to entrepreneurship, (e) writing creatively on entrepreneurship. Manifest variables in the form of mental self-reliance has increased after the mentoring model of entrepreneurial incubator. This suggests that the better the model of mentoring incubator, the better it will form a mental model of the entrepreneurial independence.